THE CONTENT VALIDITTY OF THE SUMMATIVETEST OF IN THE SECOND SEMESTER OF THE FIRST YEAR STUDENTS (A Case Study of SMAN 1 Cikarang Barat,- Bekasi) - Tita Puspitasari (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACT This study aims to clarify the matter summative validitasisi created by a professional team for the firstsemester of the second year in SMAN 1 Cikarang, Bekasi. The number of items as many as 44 items, 40multiple-choice and essay 6.Forty to about 4 questions for the reading and writing problems. The method inthis study using a qualitative description that describes the suitability of matter summative SMAN 1 Cikarang,Bekasi with the syllabus and indicators. With a qualitative approach, researchers collected data by requestinga booklet summative English and in the school syllabus. In addition, the researchers also conducted interviewsto a team of teachers who made a summative test questions. Furthermore, the researchers analyzed the items,whether the matter has valisitasisi summative. The results obtained from this study proves that the questionsummative English second semester of grade nine through percentage and analisisisi have validitasisi bad. Inaddition, about summative bahasaInggris not in accordance with the existing indicators in the syllabus.Problem grains in a summative test contained only two skills are measured. Two skills that are reading andwriting. Based comprehension ideally weight to 25% listening skills, speaking skills 25%, 25% reading skills,and writing skills 25%. Thus, it can be concluded that the results of the study skills of reading reached90.91% according to the syllabus of the test means can be said to be good. Meanwhile, for the listening skillspesrentasinya only 9, 01%. It shows that the test questions are weak or invalid.Key words: validitasisi, summative tests, syllabi English